Blood pressure targets, medication consideration and special concerns in elderly hypertension part I: General principles and special considerations - Heng-Yu Pan; Po-Lung Yang; Chun-Hsien Lin; Chun-Yi Chi; Chia-Wen Lu; Tai-Shuan Lai; Chih-Fan Yeh; Michael Yu-Chih Chen; Tzung-Dau Wang; Hsien-Li Kao; Yen-Hung Lin; Mu-Cyun Wang; et al. (Journal of the Formosan Medical Association, 2025)
To achieve a consensus on optimal blood pressure (BP) targets for older adults remains challenging, necessitating a trade-off between cardiovascular benefits and the risk of impaired organ perfusion. Evidence suggests that age and frailty have a minimal influence on the cardiovascular benefits of intensive BP control in community-dwelling elderly. Nonetheless, an increased incidence of acute kidney injury with intensive BP control has been observed in octogenarians. Therefore, it is recommended to maintain systolic BP below 130 mmHg for hypertensive patients aged 65–80 years. If well-tolerated, a systolic BP target below 120 mmHg can be recommended for patients with chronic kidney disease (CKD). However, no conclusive evidence supports a stringent BP target for patients aged 80 years and older.The selection of antihypertensive medications for elderly patients requires consideration of their cardiovascular condition and potential contraindications. Combination therapy may be necessary to achieve the desired BP target. Angiotensin-converting enzyme inhibitors or angiotensin receptor blockers are the primary choices for patients with CKD. Newer generation mineralocorticoid receptor antagonists may further reduce the risk of cardiovascular or renal events in this population.In conclusion, managing hypertension in elderly patients requires a personalized approach that balances cardiovascular benefits with potential risks, considering individual health profiles and tolerability.